(Patho)physiology of cross‐sex hormone administration to transsexual people: the potential impact of male–female genetic differences. (11th December 2014) - Gooren, L. J.; Kreukels, B.; Lapauw, B.; Giltay, E. J.
Summary There is a limited body of knowledge of desired and undesired effects of cross‐sex hormones in transsexual people. Little attention has been given to the fact that chromosomal configurations, 46, XY in male‐to‐female transsexuals subjects (MtoF) and 46, XX in female‐to‐male transsexual subjects (FtoM), obviously, remain unchanged. These differences in their genomes cause sex differences in the functions of cells. This study reviews sex differences in metabolism/cardiovascular pathology, immune mechanisms, bone (patho)physiology and brain functions and examines whether they are, maybe partially, determined by genetic mechanisms rather than by (cross‐sex) hormones. There do not appear to be major genetic impacts on the changes in bone physiology. Also immune functions are rather unaffected and the evidence for an increase of autoimmune disease in MtoF is preliminary. Brain functions of transsexuals may have differed from controls before cross‐sex hormones; they do undergo shifts upon cross‐sex hormone treatment, but there is no evidence for changes in sex‐specific brain disease. The prevalence of cardiovascular disease is higher in MtoF receiving oestrogens than in FtoM receiving androgens. While type of oestrogen and route of administration might be significant, it is reasonable to speculate that nonhormonal/genetic factors play a role.